Zambia : Technical Assistance Report-Report on External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance Report on Zambia highlights the dissemination of external sector statistics during the Department for International Development-Enhanced Data Dissemination Initiative 2 Project Module 1. The mission recommended breakdowns in the International investment position (IIP) table that are of analytical relevance, such as government securities issued abroad and issued domestically, and loan liabilities of the government and other sectors. The integrated IIP is key to verifying the consistency between the positions, the transactions, and other changes. The accuracy of the components within the international reserves in the balance of payments and in the IIP can be further improved. Valuations changes in positions are being included in the balance of payments for some components, such as government external debt and reserve assets, and should be removed from transactions. In order to support progress in different work areas, the mission recommended a detailed action plan with several priority recommendations.